2014
DOI: 10.1111/jocs.12329
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment for Nontraumatic Rupture of the Descending Thoracic Aorta: Long-Term Results

Abstract: Background This study evaluated the long‐term results of thoracic endovascular aortic repair (TEVAR) of nontraumatic rupture of the descending thoracic aorta. Methods This was a retrospective and observational single‐center study. During the 10‐year study period, 21 patients (6 males) with an average age of 66.1 ± 12.4 (range 31–81) years underwent emergency TEVAR for nontraumatic rupture of the descending thoracic aorta. The underlying aortic pathologies causing the rupture were degenerative aneurysms in 11 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In the case of non-optimal aortic coverage, a secondary procedure must be performed to improve long-term results in stable patients, and should not be considered as failure of TEVAR. 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of non-optimal aortic coverage, a secondary procedure must be performed to improve long-term results in stable patients, and should not be considered as failure of TEVAR. 5…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the setting of this specific complication, questions remain about the role and length of the stent graft: is coverage of the proximal entry tear sufficient only to stop bleeding or should the stent graft cover the entire dissected aorta with the increased risk of paraplegia? 4,5 The aim of this study is to assess the short-and mid-term results of endovascular stent graft management of acute type B aortic dissections complicated by rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Although open surgical repair remains the traditional treatment of rDTAA, TEVAR is a minimally invasive approach that does not requires thoracotomy, aortic cross-clamping, systemic heparin, cardiopulmonary bypass, or hypothermic cardiac arrest. 7 , 8 Moreover, TEVAR enables safe and effective aneurysm exclusion, can be used for treatment of patients in critical conditions, and is associated with shorter operating times, minimal additional blood loss, and lower fluid requirements. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…A study by Desai et al [29] has reported a survival rate of TEVAR equivalent to OR in patients with rDTAA at 8-10 years of follow up. In a later study by Botsios et al [21] , the rate of re-intervention is thought to be between 4.5%-16% at 1.5-44 months follow up time. Interestingly this rate reported to be as high as 45.5% after rDTAA in some other studies [6,18] .…”
Section: Open or Endovascular Repair For Rdtaa?mentioning
confidence: 95%
“…Although TEVAR seems an attractive option for managing patients with rDTAA, it cannot be used as a standard management in every patient at the time of presentation due to many factors [3] . Initially the gold standard method for managing such patients was OR [19] , however this method has been challenged by the evolution of TEVAR and the favourable short-term outcomes [16,20,21] . One of the key factors in choosing TEVAR over OR, is the anatomic variations and suitability for TEVAR.…”
Section: Is Everyone a Candidate For Tevar?mentioning
confidence: 99%